2021
DOI: 10.21037/apm-21-1281
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in patients with severe lung cancer: a narrative review

Abstract: Objective: At present, there are several guidelines for cancer complicated with VTE, but there is no specific recommendation for the treatment of lung cancer complicated with VTE. Whether is necessary to explore treatment and prevention of VTE in lung cancer.Background: Venous thromboembolism (VTE) is a common complication of severe lung cancer that can entail many adverse effects for patients. The incidence of VTE is higher in patients with lung cancer than in those with other kinds of solid tumors, and it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Esta patología se presenta en individuos diagnosticados con cáncer pulmonar, adenocarcinoma metastásico avanzado y enfermedad relacionada con el catéter venoso central o quimioterapia a largo plazo, entre otras (Zheng et al, 2021;Sosa et al, 2021;Kenmotsu & Notsu, 2021;Mosarla & Qamar, 2019;Alfonso & Inguanzo, 2020;Khorana et al, 2021). El TEV está relacionado con una morbilidad y letalidad considerables, disminuye la calidad de vida y puede conducir a la interrupción o suspensión del tratamiento del cáncer.…”
Section: Introductionunclassified
“…Esta patología se presenta en individuos diagnosticados con cáncer pulmonar, adenocarcinoma metastásico avanzado y enfermedad relacionada con el catéter venoso central o quimioterapia a largo plazo, entre otras (Zheng et al, 2021;Sosa et al, 2021;Kenmotsu & Notsu, 2021;Mosarla & Qamar, 2019;Alfonso & Inguanzo, 2020;Khorana et al, 2021). El TEV está relacionado con una morbilidad y letalidad considerables, disminuye la calidad de vida y puede conducir a la interrupción o suspensión del tratamiento del cáncer.…”
Section: Introductionunclassified
“…8,9 Many studies have showed that the prevalence of VTE is increased significantly among lung cancer patients, and It has been reported that patients with lung cancer are more likely to develop thrombotic events than other cancer patients, with an incidence of 13.9%. 10,11 VTE can appear before cancer diagnosis, and before the begin of lung cancer treatment, the related mechanism may be that patients are in a hypercoagulable state. 12 One study reported that among 231 cases of lung cancer patients before surgery, the incidence of VTE on admission was 5.2% (12/231).…”
Section: Introductionmentioning
confidence: 99%
“…Recent study on the 499 092 patients revealed ninefold higher and increased risk of VTE in cancer patients compared to the general population ( Mulder et al, 2021 ). Recent studies are suggesting development of specific recommendation for treating cancer types complicated with VTE ( Zheng et al, 2021 ). It was estimated that 1.6–20% of cancer patients encounter VTE at any time during the disease course ( Gran et al, 2018 , Mohammed et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%